TURKISH ANTI-PROVERBS IN SOCIAL MEDIA DISCOURSE - Öznur USTA TUZCU (Fırat University, 2019)
Proverbs are considered to be a universal genre of tradition that reveals the life-world and cultural values of the people of a given society, as well as their attitudes towards their surroundings. Due to the characteristic of being succinct, individuals use proverbs to convey their attitudes, opinions, beliefs and such on social media. However, the proverbs may lose their traditional forms; they are twisted and changed in many ways: by replacing words, extending the traditional proverbs, eliciting or adding extra words to the original proverbs which means they have become the modified version of proverbs that are full of satire, irony, and humor and known as “anti-proverb” in the field of Paremiology. This article deals with the structural and semantic changes applied in traditional proverbs to convey the new opinions and moral regarding the power, function, and effects of social media. The primary data source of this article includes anti-proverbs used on the social networking sites, Twitter and Facebook, which provide plentiful material for this kind of search. Out of 1368 anti-proverbs, 53 anti-proverbs have been determined as related to social media and social networking sites based on their lexis content. 11 anti-proverbs which have been derived from 9 traditional proverbs have been illustrated in this study. The selected anti-proverbs are based on especially the relationship of people in Turkish society; the power of social networking sites; the addiction to these sites. This study has revealed that the new content conveyed by the anti-proverbs expresses the relationship between people has become more virtual; the power of social media in reaching a vast amount of users in a short period and effectively is vast; whatever is shared on social media remains there contrary to oral speech.